Composition and Stability of the Vaginal Microbiota of Pregnant Women With Inflammatory Bowel Disease - Hill, Janet E; Peña-Sánchez, Juan-Nicolás; Fernando, Champika; Freitas, Aline C; Withana Gamage, Niradha; Fowler, Sharyle (Inflammatory bowel diseases, 2022)
Abstract Background Inflammatory bowel disease (IBD) is common in women of childbearing years, and active IBD during pregnancy is associated with increased rates of preterm delivery and low-birth-weight newborns. Changes in the vaginal microbiome have been associated with preterm delivery. We aimed to determine the taxonomic composition of the vaginal microbiota at 3 time points during pregnancy in a population of women with IBD. Methods Participants were recruited from the patient registry of the Preconception and Pregnancy IBD Clinic at Royal University Hospital in Saskatoon, Canada. Self-collected vaginal swabs were obtained from patients at each trimester. Microbiota profiles were created by cpn60 amplicon sequencing. Results We characterized the vaginal microbiota of 32 pregnant participants with IBD (33 pregnancies) during each trimester. A total of 32 of 33 pregnancies resulted in a live birth with 43.8% (n = 14 of 32, 2 missing) by caesarean section; 2 of 32 were preterm. Microbiota compositions corresponded to previously described community state types, with most participants having microbiota dominated by Lactobacillus crispatus. In 25 of 29 participants in which samples were available for more than 1 time point, there was no change in the community state type over time. Prevalence of Mollicutes (Mycoplasma and/or Ureaplasma) was significantly higher in pregnant participants with IBD than in a previously profiled cohort of 172 pregnant women without IBD who delivered at term. Conclusions The vaginal microbiome of participants with IBD was stable throughout pregnancy. Prevalence of Mollicutes, which has been associated with preterm delivery, warrants further study in this patient group. Lay Summary Composition of the vaginal microbiota was stable throughout pregnancy. Prevalence of Mollicutes was significantly higher in individuals with inflammatory bowel disease than in a previously profiled cohort of 172 pregnant women without inflammatory bowel disease who delivered at term.